0954 Association between Sleep Disturbance in Alzheimer's Disease Patients and Burden on and Health Status of Their Caregivers. (12th April 2019) - Okuda, Shoki; Tetsuka, Jumpei; Takahashi, Kenichi; Toda, Yasuo; Kubo, Takekazu; Tokita, Shigeru
Abstract: Introduction: Sleep disturbance in Alzheimer's disease (AD) patients may have a negative impact not only on patients themselves but also on the physical and mental health of their caregivers. This study investigated the association between sleep disturbance in AD patients and the burden imposed on the caregivers and their health status in Japan. Methods: We conducted a cross-sectional web-based questionnaire survey among caregivers of AD patients with insomnia symptoms in Japan. Demographic data and sleep disturbance of AD patients (Sleep Disorders Inventory (SDI)), burden (Burden Index of Caregivers-11 [BIC-11]) and health status of caregivers, including sleep quality (Pittsburgh Sleep Quality Index), depressive state (Patient Health Questionnaire-9) and physical/mental quality of life (12-Item Short Form Health Survey), were collected. Multivariate analysis was used to examine the association between the burden and health status of caregivers and sleep disturbance in their care recipients with AD. Results: A total of 496 caregivers of AD patients with insomnia symptoms were examined in this study. We found that the BIC-11 total score increased as the SDI score increased, indicating a significant positive association, even after adjusting for confounding factors. Similar patterns were observed for subdomain of BIC-11 (time-dependent, emotional, existential, physical, service-related, and total care burdens). We also found an association between sleep disturbances of AD patients and health of caregivers. Conclusion: This study demonstrated that sleep disturbance in AD patients was associated with an increased burden and poorer health status of caregivers, suggesting the importance of understanding sleep disturbances in AD patients. Traditionally, sleep disturbances in AD patients have been treated as a part of the BPSD (behavioral and psychological symptoms of dementia) spectrum; however, our results suggest the importance of focusing on sleep disturbances from the perspective of their burden on caregivers and the impact on their health. Support (If Any): This study was funded by MSD K.K., Tokyo, Japan